'Studies have shown that …' how to read a statistical study. (24th May 2017) - Daniels, John E.
Summary: This article provides some background for a classroom discussion of statistical research studies. The history of cigarettes and warning labels in the USA is reviewed here in order to demonstrate the challenges of statistical research and communication.